The Effectiveness of Rational Emotive Behavior Therapy Counseling to Increase Self Esteem of Slow Learner Children - Nurshobah, Devi; Awalya, Awalya; Sunawan, Sunawan (Universitas Negeri Semarang, 2021)
One of the measures to accommodate the learning needs of slow learner students is as a form of support for the inclusion paradigm in schools. Learning that is attempted by the teacher is an effort to condition slow learner students according to their learning needs. The purpose of this study was to test the effectiveness of Rational Emotive Behavior Therapy counseling to increase the Self Esteem of Slow Learner Children in Inclusion Schools SMP Negeri 15 Cirebon. . To achieve such objective, the study used single subject design with the pattern of multiple baseline across individuals done in eleven sessions of observation, namely 3 baseline A1 sessions, 5 times intervention session, and 3 baseline A2 sessions. For more, the subjects of this study were two indicated experiencing self esteem. In this state, behavior target was reduced from self esteem behavior. Meanwhile, the data of the observed subjects were collected thorough direct observation method with Goal Attainment Scale guides. Further, visual graph analyses were carried out to look for mean, the degree of level of performance, rapidity behavior change, the trend of performance, stability levels, and overlap data which were then followed by T score and z score calculations. The results showed that Rational Emotive Behavior Therapy counseling was able to increase self esteem. For further research, you can use a reversal design pattern so that it can be seen about the comparison of the two baseline conditions before and after the intervention so that the effect of consistent behavior change in the intervention phase can be revealed more deeply